DIGITALIZATION OF PROJECT MANAGEMENT IN UZBEKISTAN AND FOREIGN EXPERIENCE - A. Kenjabaev; B. Sadriddinov (Modern American Journals, 2025)
The article discusses project management in the digital economy, implying the use of well-known and widely used in modern technologies methods and tools such as the use of Artificial Intelligence (AI), the use of cloud tools and flexible methodologies for planning, execution and control of projects related to the digitalization of business, IT development, creation of digital infrastructure and the provision of online services.
Keywords: Artificial intelligence, cloud tools, flexible technologies, planning and control of project implementation process.